VD_FINDINFO Jug / 2023 / 421 vom 11. Februar 2022 - VD Tribunal cantonal (2022)
INDEMNITÉ POUR DÉTENTION, INDEMNITÉEN GÉNÉRAL, FRAIS DE LA PROCÉDURE | 51 CP, 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH), 442 al. 4 CPP (CH)